Adverse Reactions of the Second Dose of the BNT162b2 mRNA COVID-19 Vaccine in Healthcare Workers in Korea - Lee, Yun Woo (J Korean Med Sci, 2021)
We conducted a prospective, mobile-based survey on the self-reported adverse reactions in healthcare workers (HCWs) who received both doses of the BNT162b2 mRNA vaccine. Of the 342 HCWs who completed the two-dose vaccination, 265 (77.5%) responded to the survey at least once. Overall, the rates of adverse reactions were higher after the second dose compared with the first dose (89.1% vs. 80.1%, P = 0.006). The most common systemic reactions were muscle ache (69.1%), fatigue (65.7%), headache (48.7%), chills (44.2%), and fever (32.1%), and were notably more common after the second dose vaccine as well. We also noted a sex difference in which the frequency of adverse reactions after the second dose of the vaccine was significantly higher in females, which was not observed after the first dose. The rates of adverse reactions were lower in older age groups, and the rates and severities of the adverse reactions decreased during the 3-day period following vaccination.